Behavioral processes and social influences on the development of stone-tool use in long-tailed macaques - Tan, Amanda Wei Yi (2016)
Coastal populations of macaques maintain rare stone-tool-use traditions for exploiting shellfish. I provide the first examination of macaque tool-use development on Koram Island (N = 69), Khao Sam Roi Yot National Park, Thailand. Macaques perform simple exploratory manipulations from 1-2 months. Around 1.5 years, combinatory manipulations, including ineffective percussion and object-action sequences predominate until competence is achieved between 2.5-3.5 years. Mastering percussion and relating objects, particularly in three-item combinations (stone-shellfish-anvil vs. stone-sessile oyster), are challenging for macaques. Young macaques engage in tool-related interactions with tool users (e.g. scrounging, observing) preferentially according to tool-users’ skill in addition to social relationships. Their interactions, and social learning opportunities influenced by maternal behaviour and sociality, affected developmental speeds, and social relationships related to similarity in tool users’ hammering patterns and food choices. Understanding how macaques interact with their physical and social environments to develop tool-use skills, contributes to broader discussions of cultural evolution.